PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT MEDAN MARELAN - Dinaria Br Sembiring (LPPM STIE EKA PRASETYA, 2019)
The purpose of this study was to determine the effect of leadership style, work motivation on employee performance at the Medan Marelan District Office. The population and sample used in this study were employees of the Medan Marelan sub-district office as many as 50 respondents. The type of data used are primary data and secondary data obtained through interviews, questionnaires and literature studies that are measured using a Likert scale. Hypothesis testing in this study uses a validity test analysis tool, data analysis conducted in this study is the hypothesis test with t test (partial test) and F test (simultaneous test). The results of this study were obtained that: (1) based on a partial test of leadership style Influenced the performance of Marelan district office staff with a t test of 2.562. (2) Based on a partial test of work motivation, the effect on the performance of Marelan district office staff with a t test of 3.796. (3) Based on the Simultaneous test the Effect of Work Motivation and Work Competence on the Performance of the Employees of Medan Marelan Sub-District Office with an F test of 425,327.